PENGARUH MENTAL ACCOUNTING DAN LITERASI KEUANGAN TERHADAP FINANCIAL BEHAVIOUR DENGAN DIMEDIASI GAYA HIDUP KONSUMTIF MAHASISWA AKTIF DI DKI JAKARTA - Ismia, Fani Kesya; Udzikrilah, Sinta; Pratiwi, Permata Dian (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This research explores the influence of Mental Accounting and Financial Literacy on Financial Behavior, mediated by Consumer Lifestyle, using a sample of active students in DKI Jakarta. SmartPLS 4 is utilized to analyze the research model, with SEM (Structural Equation Modeling) employed to test the hypotheses. The study involves 217 respondents from active students in DKI Jakarta. The research examines three variables: Mental Accounting and Financial Literacy as independent variables, Financial Behavior as the dependent variable, and Consumer Lifestyle as the mediating variable. The objective is to understand how students' mental accounting practices and financial literacy levels impact their financial behaviors, with consumer lifestyles influencing these relationships. Findings are expected to provide insights into the financial decision-making processes of young adults in an educational setting, contributing to more effective financial education programs and interventions. This study emphasizes the significant role of lifestyle in shaping financial behaviors, offering a comprehensive view of the factors affecting financial behavior among students, and aims to enhance financial behavior through targeted improvements in financial literacy and lifestyle awareness.